Observation of Bragg polaritons in monolayer tungsten disulphide - Wang, Xu; Wu, Lishu; Zhang, Xuewen; Yang, Weihuang; Sun, Zheng; Shang, Jingzhi; Huang, Wei; Yu, Ting (Nano research, 2022)
Strong light-matter interactions involved with photons and quasiparticles are fundamentally interesting to access the wealthy many-body physics in quantum mechanics. The emerging two-dimensional (2D) semiconductors with large exciton binding energies and strong quantum confinement allow to investigate exciton-photon coupling at elevated temperatures. Here we report room-temperature formation of Bragg polaritons in monolayer semiconductor on a dielectric mirror through the exciton-Bragg photon coupling. With the negative detuning energy of ∼ 30 meV, angle-resolved reflection signals reveal anti-crossing behaviors of lower and upper polariton branches at ±18° together with the Rabi splitting of 10 meV. Meanwhile, the strengthened photoluminescence appears in the lower polariton branch right below the anti-crossing angles, indicating the presence of the characteristic bottleneck effect caused by the slowing exciton-polariton energy relaxation towards the band minimum. The extracted coupling strength is between the ones of weak and distinct strong coupling regimes, where the eigenenergy splitting induced by the moderate coupling is resolvable but not large enough to fully separate two polaritonic components. Our work develops a simplified strategy to generate exciton-polaritons in 2D semiconductors and can be further extended to probe the intriguing bosonic characteristics of these quasiparticles, such as Bose-Einstein condensation, polariton lasing and superfluidity, directly at the material surfaces.